Rozvoj konkurenceschopnosti firmy Jirasgames a.s. - Lelek, Jakub (Vysoké učení technické v Brně. Fakulta podnikatelská, 2015)
Diplomová práce s názvem Rozvoj konkurenceschopnosti firmy Jirasgames, a.s. se zaměřuje na návrhy vedoucí k zvýšení konkurenceschopnosti a celkovému rozvoji firmy. Cílem mé práce je posoudit současný stav společnosti za pomoci teoretických znalostí čerpaných v z odborné literatury. Navrhnout řešení směřující k rozvoji konkurenceschopnosti a následně vyhodnotit přínosy.

The diploma thesis called Competitiveness Development of Jirasgames, a.s. focuses on proposals leading to enhancing competitiveness and overall development of the company. The main aim of the thesis is to evaluate the current state of the company, which is done based on the theoretical background gained in specialized literature. The next aim is to propose solutions leading to competitiveness development and consequently evaluate its benefits
Development of Business Competitiveness of Jirasgames a.s.
Keywords: Konkurenceschopnost; konkurence; hodnotový řetězec; konkurenční strategie; propagace; distribuce; trh; zákazník; competitiveness; competition; value chain; competitive strategies; promotion; distribution; market; customer